HOMEOPATHIC APPROACH TO PRIMARY DYSMENORRHEA MANAGEMENT: A CASE REPORT - DR. SHWETA MOHANBHAI PATEL; DR. RAKESH GOHEL (The Bioscan, 2025)
Primary dysmenorrhea (PD) is a common condition among females, significantly impacting their quality of life and academic performance due to frequent absences. These absences, often caused by experiences like menstrual pain, can have adverse effects on students' educational achievements. Dysmenorrhea, characterized by painful menstruation, is a frequent complaint among women seeking medical help. It manifests as either sharp or dull pelvic or lower abdominal pain. Primary dysmenorrhea (PD) specifically affects healthy women without pelvic organ abnormalities, predominantly occurring in adolescent girls. In contrast, secondary dysmenorrhea arises from pelvic pathology and may require surgical intervention. Treatment for PD often involves the use of homeopathic medicines, including constitutional anti-miasmatic and specific remedies, which have shown considerable efficacy. Case summary: This was a case of a primary dysmenorrhea in a patient aged 20-year presented to Homoeopathic hospital at outpatient department received individualized homoeopathic remedy. She had intense periodic pain in lower part of abdomen during menses over the last 5 years. And she used to take pain killers for relief. Homoeopathic treatment was started with Liium Tigrinum and later on Sepia on the basis of totality of symptoms and reportorial analysis. Which showed reduction in pain much more than before and overall improvement was seen in patient. Intensity of pain was measured by using a visual analogue scale (VAS). This evidence-based case which was reported in accordance with HOM CASE guidelines indicated that individualized homoeopathic remedies can be safely used to treat condition like primary dysmenorrhoea.